LOOKING TO LITERATURE FOR TRANSFORMATION (The Pretoria Student Law Review, 2021)
The English literature that is being taught to law students plays a role in shaping critical and ethically conscious lawyers, as well as in contributing to a transformative approach to legal education in post1994 South Africa by engaging with different perspectives. Value lies in engaging specifically with previously devalued perspectives in a substantive way.5 While limited progress has been made to include diverse and previously undervalued perspectives, a more inclusive English syllabus will produce more ethically conscious and humanistic law students and lawyers.6 Incorporating more literature of marginalised groups into the law syllabus in a non-hierarchical way will challenge and perhaps begin to dismantle the pre-democratic dominance of structural and psychological oppression, systems of patriarchy, and the black inferiority complex.7
Keywords: English literature; inclusive English syllabus; law students; marginalised groups; psychological oppression